Designing the User Interface (UI) for a Mobile-Based Ordering System at Burger Stalls - Alfariz, Risandi; Zikri Ezza Alhira, (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
The development of mobile technology has encouraged culinary businesses to improve service quality through the use of digital systems, including in the ordering process. Warung Burger Zidan, as a small-scale culinary business, still uses a manual ordering system that has the potential to cause recording errors, service delays, and order discrepancies. This study aims to design a simple, easy-to-use mobile-based ordering system user interface (UI) that suits the operational characteristics of a burger restaurant. The research method used is qualitative with data collection techniques in the form of literature studies, interviews, and observations. The UI design process was carried out using a User-Centered Design (UCD) approach that placed user needs and characteristics as the main focus of the design. The results of the study are a mobile ordering application interface design that includes a menu display, shopping cart, automatic price calculation, and cash and QRIS payment method options. The design evaluation shows that the resulting UI design is capable of supporting a more structured ordering process, increasing service efficiency, and minimizing the risk of recording errors. This study is expected to be the basis for the development of a digital ordering system for small-scale culinary businesses.